Repair material and constrained interface construction method thereof
By using expansion and extrusion alkali-excited slag fly ash material and groove treatment technology, the problems of low bonding interface strength and poor performance in concrete structure repair are solved, and the tensile strength and anti-chlorine ion penetration performance are significantly improved. A wide range of concrete repair applications.
Patent Information
- Application Number
- CN202411624409.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, when repairing concrete structures, the bonding interfaces of new and old concrete are low, have poor performance, and the effect is not good after using expansion agent.
Use expansion and extrusion alkali-activated slag fly ash as repair material, prepare it through a specific ratio of raw materials, add HCSA or MgO expansion agent, and perform groove processing to improve the tensile strength of the cleavage and chloride ion permeability of the interface. .
It significantly improves the tensile strength of the repaired bond surface and the anti-chlorine ion penetration properties, inhibits the self-contraction of the new concrete, and can better fill the grooves and pores of the old concrete, improving the repair effect.
Smart Images

Figure CN119118585A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of repairing concrete building structures, and in particular to a repairing material and a constrained interface construction method thereof. Background Art
[0002] Many concrete structures are facing repairs nowadays. The bonding area between the repair material and the old concrete structure is a weak area in the structure, which is related to the long-term performance of the entire structure. Water leakage and steel corrosion that occur during the use of concrete structures are often related to the bonding surface between the new and old concrete. The current conventional method is to use a higher grade of concrete for repair, but many actual engineering practices have shown that the bonding interface strength of the new and old concrete repaired by conventional maintenance methods is low and the performance is poor. In order to improve the effect of the repair, the prior art began to try to use expansive agent-added concrete for repair, but the actual effect is very unsatisfactory. After adding the expansive agent, the performance of the repair material may deteriorate. Therefore, a new repair material and its corresponding construction method are needed to solve the problems of low bonding interface strength, poor performance and poor effect in the prior art. Summary of the invention
[0003] In view of this, an embodiment of the present invention provides a repair material and a constrained interface construction method thereof, which solves the problems of low bonding interface strength, poor performance and poor effect of the existing method.
[0004] According to the first aspect, an embodiment of the present invention provides a repair material, which is an expansive extruded type alkali-activated slag fly ash. The raw materials include: sand, gravel, alkali activator, slag, fly ash, water, and an expansive agent. The raw materials are prepared according to weight to determine the expansive extruded type alkali-activated slag fly ash.
[0005] In combination with the first aspect, in a first embodiment of the first aspect, the alkaline activator consists of water glass and sodium hydroxide.
[0006] In combination with the first embodiment of the first aspect, in the second embodiment of the first aspect, the modulus of the alkaline activator is 1.3, and the specific preparation ratio is: 147.2 parts of the water glass and 23.9 parts of the sodium hydroxide.
[0007] In combination with the first embodiment of the first aspect, in the third embodiment of the first aspect, the raw materials are prepared by weight to determine the expanded extruded alkali-activated slag fly ash, including: The expansive extrusion type alkali-activated slag fly ash is prepared in the proportion of 520 parts of sand, 965.5 parts of gravel, 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide, 104.5 parts of water and 25-75 parts of the expansion agent to improve the splitting tensile strength and chloride ion permeability resistance of the repair interface.
[0008] In combination with the first aspect, in a fourth embodiment of the first aspect, the expansion agent is an HCSA expansion agent, and the preparation quantity is 50 parts.
[0009] In combination with the first aspect, in the fifth implementation of the first aspect, the expansion agent is MgO expansion agent, and the preparation quantity is 50 parts.
[0010] The repair material provided by the embodiment of the present invention, the prepared slag fly ash geopolymer mixed with 50 parts of HCSA expansion agent has the characteristics of high splitting tensile strength and good chloride ion permeability resistance under the condition of interface grooving treatment. Compared with no expansion agent added and no constraint maintenance, the splitting tensile strength is 65.8% higher and the chloride ion permeability resistance is 56.3% higher, which significantly improves the performance of the repaired bonding surface. Moreover, after adding this expansion agent, on the one hand, the self-shrinkage of the new concrete is suppressed, and on the other hand, the new concrete can better fill the grooves and pores of the old concrete. It can be widely used in concrete repair and has a prospect of promotion and application.
[0011] According to the second aspect, the constrained interface construction method of the repair material provided by the embodiment of the present invention includes: Prepare a repair material according to any implementation of the first aspect of this embodiment; Perform grooving on the interface of the geopolymer to be repaired to determine the target repair interface; The repair material is applied at the target repair interface to repair the geopolymer to be repaired.
[0012] In combination with the second aspect, in the first implementation of the second aspect, the groove width and groove depth of the grooving process are both half of the maximum particle size of the coarse aggregate.
[0013] In combination with the second aspect, in a second implementation of the second aspect, grooves are formed on all four sides of the geopolymer interface to be repaired.
[0014] The constrained interface construction method of the repair material provided in this embodiment, the slag fly ash geopolymer mixed with 50 parts of HCSA expansion agent has the characteristics of high splitting tensile strength and good chloride ion permeability resistance under the condition of interface groove treatment. Compared with no expansion agent added and no constraint maintenance, the splitting tensile strength is 65.8% higher and the chloride ion permeability resistance is 56.3% higher, which significantly improves the performance of the repaired bonding surface. Moreover, after adding this expansion agent, on the one hand, the self-shrinkage of the new concrete is suppressed, and on the other hand, the new concrete can better fill the grooves and pores of the old concrete. It can be widely used in concrete repair and has a prospect of promotion and application.
[0015] According to the third aspect, an embodiment of the present invention provides an electronic device, comprising: a memory and a processor, the memory and the processor being communicatively connected to each other, the memory storing computer instructions, and the processor executing the constrained interface construction method of the repair material described in the second aspect or any one of the embodiments of the second aspect by executing the computer instructions.
[0016] According to the fourth aspect, an embodiment of the present invention provides a computer-readable storage medium, which stores computer instructions, and the computer instructions are used to enable the computer to execute the constrained interface construction method of the repair material described in the second aspect or any one embodiment of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is a flow chart of a constrained interface construction method of a repair material according to an embodiment of the present invention; Figure 2 is a schematic diagram of a slotting process according to an embodiment of the present invention; Figure 3 It is a schematic diagram of the hardware structure of an electronic device provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0020] In this embodiment, a repair material and a corresponding interface treatment process, namely, grooving, are provided. A reasonable grooving process is used to constrain the direction of expansion and deformation of the repair material so that the expansion develops toward the repair interface, thereby achieving the purpose of automatically squeezing the repair interface, thereby further improving the performance of the concrete structure repair interface and enhancing the effect of interface repair.
[0021] The repair material is an expansive extruded alkali-activated slag fly ash, and the raw materials include: sand, gravel, alkali activator, slag, fly ash, water, and an expander. The raw materials are prepared according to weight to determine the expansive extruded alkali-activated slag fly ash. The expansive extruded alkali-activated slag fly ash is prepared according to the proportion of 520 parts of sand, 965.5 parts of gravel (maximum particle size 20mm), 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide, 104.5 parts of water, and 25-75 parts of the expander to improve the splitting tensile strength and chloride ion permeability resistance of the repair interface.
[0022] Specifically, the alkaline activator is composed of water glass and sodium hydroxide. The alkaline activator includes 23.9 parts of solid NaOH and 47.8 parts of water to prepare a NaOH solution, during which the water is slowly added along the wall of the beaker and stirred continuously; and then the alkaline activator modulus is adjusted to 1.3 by adding 147.2 parts of water glass. The alkaline activator needs to be prepared 24 hours in advance.
[0023] As a further improvement of the present invention, slag fly ash, sand and stone can be taken out and fully mixed according to the usage specifications of 520 parts of sand, 965.5 parts of stone, 225 parts of slag and 225 parts of fly ash. After the above materials are evenly mixed, the expansion agent is added and fully mixed; when stirring the above materials, the prepared alkali activator is added and stirred; the remaining water is added and fully stirred to obtain the expansion extrusion type alkali-activated slag fly ash geopolymer repair material.
[0024] In a specific embodiment, the expansion agent is HCSA expansion agent. The amount of expansion agent added is 50 parts. Regarding the selection of expansion agent, the present invention conducted an exploratory comparative test of various expansion agents currently available on the market. The determination method is to study the effects of the expansion agent type (including 4 types, namely gypsum, UEA, MgO, and HCSA), the expansion agent dosage (0, 25, 50, and 75 parts), and whether constraints are applied on the tensile strength and impermeability of the repair interface through exploratory tests. The exploratory test obtained the following results: The study found that when 50 parts of HCSA expansion agent is used and curing is performed under constraints, the splitting tensile strength and chloride ion penetration resistance are the best. The splitting tensile strength can reach 2.52MPa, and the chloride ion permeability coefficient can reach 4.60×10-12m2 / s. Compared with no expansion agent and no curing under constraints, the splitting tensile strength is 65.8% higher and the chloride ion penetration resistance is 56.3% higher. When 50 parts of MgO expansion agent is used for curing under constraints, the splitting tensile strength effect and chloride ion penetration effect are second only to the use of 50 parts of HCSA expansion agent, and the effect is also good.
[0025] The concrete structure geopolymer repair material provided by the embodiment of the present invention has the characteristics of high splitting tensile strength and good chloride ion permeability resistance when the interface is grooved. Compared with no expansion agent added and no constraint maintenance, the splitting tensile strength is 65.8% higher and the chloride ion permeability resistance is 56.3% higher, which significantly improves the performance of the repaired bonding surface. Moreover, after adding this expansion agent, the self-shrinkage of the new concrete is suppressed on the one hand, and the grooves and pores of the old concrete can be better filled by the new concrete on the other hand. It can be widely used in concrete repair and has a prospect of promotion and application.
[0026] In this embodiment, a constrained interface construction method of a repair material is provided, which can be used in electronic devices such as computers, mobile phones, tablet computers, etc. Figure 1 FIG. 1 is a flow chart of a constrained interface construction method of a repair material according to an embodiment of the present invention. Figure 1 As shown, the process includes the following steps: S11, prepare the repair material as in the above embodiment. Prepare the repair material according to the fixed ratio and preparation requirements. The detailed information has been determined in the above embodiment and will not be repeated in this embodiment.
[0027] S12, performing grooving processing on the interface of the geopolymer to be repaired to determine the target repair interface.
[0028] The interface treatment method is grooving; the groove width and groove depth are both 10-15mm; the location of the groove should be preferably in the vertical direction where the penetration path is short, and when conditions permit, grooves should be made on all four sides of the repair interface. Regarding the constrained interface treatment method, the present invention is obtained through exploratory comparative tests of multiple interface treatment methods. The exploratory test includes five interface treatment methods: no treatment, wire brushing, point pit type artificial regular chiseling, direct splitting and grooving. The depth of the groove is determined by comparing the average depth of the aggregate exposed by splitting.
[0029] After the test, it was concluded that: the surface roughness of the old concrete treated by the groove is the largest, indicating that its restraint ability may be the best; the interface repaired by the groove treatment has the best splitting tensile performance, which further shows that the restraint effect of the groove treatment may be the best among the five interface treatment methods. Therefore, the present invention conducted further exploratory tests to test the influence of different groove sizes. There are 4 different groove widths, which are respectively set to 5mm, 10mm, 15mm, and 20mm, and the groove depth is fixed to half of the maximum particle size of the coarse aggregate of the repair material: 10mm. The above-mentioned expansion extrusion type repair material is used to repair the grooved interface to conduct splitting tensile tests and chloride ion penetration resistance tests to obtain the groove size with the best effect. See the groove method. Figure 2 , the test results are shown in Table 1.
[0030] Table 1 Slotting test results
[0031] The test shows that when the width and depth of the slots for repair interface treatment are 10-15mm, the splitting tensile strength and chloride ion permeability coefficient are optimal. This size is the optimal slot size. At the same time, by comparing with the coarse aggregate particle size, it can be seen that the slot width and slot depth are about half of the maximum particle size of the coarse aggregate. Therefore, it is recommended that the slot size should not exceed half of the maximum particle size of the coarse aggregate of the repair material, where the maximum particle size of the coarse aggregate is a known size.
[0032] S13, applying the repair material to the target repair interface to repair the geopolymer to be repaired.
[0033] In this embodiment, grooves are cut on the old concrete interface before repair (groove depth is 10 mm, groove width is 10 mm), grooves are cut on all four sides of the repair interface, and the number of grooves on each side is determined comprehensively according to the size of the repair interface and the groove spacing of 10 mm; then, the dust is washed off with water; the repair material is applied, and standard maintenance is performed.
[0034] The concrete structure geopolymer repair material and repair method provided in this embodiment, the slag fly ash geopolymer mixed with 50 parts of HCSA expansion agent has the characteristics of high splitting tensile strength and good chloride ion permeability resistance under the condition of interface groove treatment. Compared with no expansion agent added and no constraint maintenance, the splitting tensile strength is 65.8% higher and the chloride ion permeability resistance is 56.3% higher, which significantly improves the performance of the repaired bonding surface. Moreover, after adding this expansion agent, on the one hand, the self-shrinkage of the new concrete is suppressed, and on the other hand, the new concrete can better fill the grooves and pores of the old concrete. It can be widely used in the repair of concrete and has a prospect of promotion and application.
[0035] The present invention also provides an electronic device. Figure 3 , Figure 3 is a schematic diagram of the structure of an electronic device provided by an optional embodiment of the present invention, such as Figure 3 As shown, the electronic device may include: at least one processor 601, such as a CPU (Central Processing Unit), at least one communication interface 603, a memory 604, and at least one communication bus 602. The communication bus 602 is used to realize the connection and communication between these components. The communication interface 603 may include a display screen (Display), a keyboard (Keyboard), and the optional communication interface 603 may also include a standard wired interface and a wireless interface. The memory 604 may be a high-speed RAM memory (Random Access Memory, volatile random access memory) or a non-volatile memory (non-volatile memory), such as at least one disk storage. The memory 604 may optionally be at least one storage device located away from the aforementioned processor 601. The processor 601 may be combined with Figure 3 In the described device, the memory 604 stores an application program, and the processor 601 calls the program code stored in the memory 604 to execute any of the above method steps.
[0036] The communication bus 602 may be a peripheral component interconnect (PCI) bus or an extended industry standard architecture (EISA) bus. The communication bus 602 may be divided into an address bus, a data bus, a control bus, etc. For ease of representation, Figure 3 Only one thick line is used in the diagram, but this does not mean that there is only one bus or only one type of bus.
[0037] Among them, the memory 604 may include a volatile memory (English: volatile memory), such as a random access memory (English: random-access memory, abbreviated: RAM); the memory may also include a non-volatile memory (English: non-volatile memory), such as a flash memory (English: flash memory), a hard disk drive (English: hard disk drive, abbreviated: HDD) or a solid-state drive (English: solid-state drive, abbreviated: SSD); the memory 604 may also include a combination of the above types of memory.
[0038] The processor 601 may be a central processing unit (CPU), a network processor (NP), or a combination of a CPU and a NP.
[0039] The processor 601 may further include a hardware chip. The hardware chip may be an application-specific integrated circuit (ASIC), a programmable logic device (PLD), or a combination thereof. The PLD may be a complex programmable logic device (CPLD), a field-programmable gate array (FPGA), a generic array logic (GAL), or any combination thereof.
[0040] Optionally, the memory 604 is also used to store program instructions. The processor 601 can call the program instructions to implement the constrained interface construction method of the repair material as shown in the embodiment of the present application.
[0041] The embodiment of the present invention further provides a non-transient computer storage medium, which stores computer executable instructions, and the computer executable instructions can execute the constrained interface construction method of the repair material in any of the above method embodiments. The storage medium can be a magnetic disk, an optical disk, a read-only memory (ROM), a random access memory (RAM), a flash memory, a hard disk (HDD) or a solid-state drive (SSD), etc.; the storage medium can also include a combination of the above types of memory.
[0042] Although the embodiments of the present invention have been described in conjunction with the accompanying drawings, those skilled in the art may make various modifications and variations without departing from the spirit and scope of the present invention, and such modifications and variations are all within the scope defined by the appended claims.
Claims
1. A repair material, It is characterized in that The repair material is an expansive extruded alkali-activated slag fly ash, and the raw materials include: sand, gravel, alkali activator, slag, fly ash, water, and an expansive agent. The raw materials are mixed according to weight to determine the expansive extruded alkali-activated slag fly ash.
2. The repair material according to claim 1, It is characterized in that The alkaline activator consists of water glass and sodium hydroxide.
3. The repair material according to claim 2, It is characterized in that The modulus of the alkaline activator is 1.3, and the specific preparation quantities are: 147.2 parts of the water glass and 23.9 parts of the sodium hydroxide.
4. The repair material according to claim 2, It is characterized in that The various raw materials are prepared according to weight to determine the expanded extruded alkali-activated slag fly ash, including: The expansive extrusion type alkali-activated slag fly ash is prepared in the proportion of 520 parts of sand, 965.5 parts of gravel, 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide, 104.5 parts of water and 25-75 parts of the expansion agent to improve the splitting tensile strength and chloride ion permeability resistance of the repair interface.
5. The repair material according to claim 1, wherein the expansion agent is HCSA expansion agent, and the preparation quantity is 50 parts.
6. The repair material according to claim 1, wherein the expansion agent is MgO expansion agent, and the preparation quantity is 50 parts.
7. A constrained interface construction method for repair materials, It is characterized in that include: Prepare the repair material according to any one of claims 1 to 6; Perform grooving on the interface of the geopolymer to be repaired to determine the target repair interface; The repair material is applied at the target repair interface to repair the geopolymer to be repaired.
8. The method according to claim 7, It is characterized in that The groove width and groove depth of the groove processing are both half of the maximum particle size of the coarse aggregate.
9. The method according to claim 8, It is characterized in that Grooving is performed on all four sides of the geopolymer interface to be repaired.
Citation Information
Patent Citations
Energy-saving type concrete crack repairing agent
CN104478371A
Pavement / bridge deck concrete fast mending material and application thereof
CN104926253A
High-performance repair cement based on alkali-activated cementing material and preparation method of high-performance repair cement
CN118529975A
Hydraulic composition
JP2010037130A
Repair-mortar material, repair-mortar composition, and curing body
WO2022230606A1
